PHYSIOLOGICAL PROFILING AND MICROORGANISMS COMMUNITY ANALYSIS IN CIANJUR TAUCO FERMENTATION - Baroroh, Septiyana
Tauco is a yellow-colored saline paste originating from Indonesia, made from fermented yellow soybeans with a meat-like flavor and used as flavoring agent. The center of Tauco production is located in Cianjur, West Java. In this study, Tauco Cap Meong from Cianjur was used as a sample. Fermentation lasts for 105 days which consists of mold fermentation and brine fermentation. Fermentation occurs traditionally and spontaneously without the addition of starter culture causing inconsistencies in the quality of tauco and cross-contamination during the fermentation. The purpose of this study is to analyze community structure and physiological profile of microorganism during tauco fermentation. Environmental parameters such as acidity level (pH) and salt content will be measured. Nutritional parameters will be determined by proximate analysis. Illumina MiSeq Sequencing used to analyze the structure of microorganism community during fermentation and Biolog EcoPlate used to conduct community level physiological profiling. A total of 6 samples were used, at 0 and 3 days fermentation (FK0 and FK3) representing mold fermentation, 6 and 14 days (FG2 and FG10) representing brine fermentation and 45 and 105 days (FL1 and FL3) representing aging stage of brine fermentation. During fermentation, the pH value decreased from 6.37 at the beginning to 5.23 at the end of fermentation, while the salt content increased from 0.002% at the beginning to 0.072% at the end of fermentation. Proximate analysis showed an increase in water content, ash content and fat content respectively from 37.09%, 2.62% and 17.93% to 49.13%, 12.21% and 18.47%, while the protein and carbohydrate content decreased, respectively from 26.3% and 16.06% to 11.9% and 8.34%. The results of the Illumina MiSeq Sequencing analysis showed that during the tauco fermentation, the bacterial community was dominated by Firmicutes in all stages, whereas at the genus level it was dominated by Geobacillus, Weissella, Bacillus, Staphylococcus and Streptococcus in mold fermentation, then Pediococcus, Weissella and Enterococcus in brine fermentation, and Enterococcus, Staphylococcus, and Geobacillus in aging stage of brine fermentation. The fungal community is dominated by the Ascomycota at all stages of fermentation, while at the genus level it is dominated by unidentified Aspergillaceae in the beginning of mold fermentation, unidentified Aspergillaceae and Trichosporon in the end of mold fermentation until the beginning of brine fermentation, and Candida at the end of brine fermentation until aging stage of brine fermentation. Diversity of bacterial communities has increased from the beginning to the end of fermentation marked by an increase in the Shannon Index and Inverse Simpson, respectively from 1.86 and 0.56 to 2.69 and 0.76, while the diversity of the fungal community has decreased marked by a decrease in the Shannon and Inverse Simpson Index, from of 0.91 and 0.23 to 0.00 for both indexes. Analysis by Biolog EcoPlate resulted in the Average Well Color Development (AWCD) score at 168s hours incubation for each sample aged 0; 3; 6; 14; 45 and 105 days in the amount of 0.095; 0.579; 0.273; 0.036; 0.037 and 0.067 respectively. This research has showed the change of microorganisms community in tauco fermentation corresponding to carbon source utilization.